Interactions Between Antimicrobial Peptides and Targets Responsible for their Nephrotoxic Action: Molecular Dynamics Simulations - Lisnyak, Yury; Martynov, Artur; Farber, Boris (Current Drug Safety, 2024)
Objectives: Polymyxin is the last line of defense against resistant forms of microorganisms, but it has significant nephrotoxicity. One of the directions in reducing the nephrotoxicity of polymyxin is to modify the charge of the molecule and accordingly, to change the topicity of the polymyxin derivative to the renal megalin. Such modification can lead to a decrease in the accumulation of polymyxin in the kidneys and reduce its toxicity while maintaining its antimicrobial properties. The study aimed to investigate the structural aspects of polymyxin nephrotoxicity at the atomic level to promote the more purposeful development of the polymyxin’s derivatives with the lower nephrotoxic action. Materials and Methods: The molecular dynamics simulations of the complexes of polymyxin B and its derivative NAB7061 (that carries only three positive charges located within the macrocycle) with megalin were performed in program package YASARA structure with explicit water (TIP3P) and ions (0.9 % NaCl) in NPT ensemble using the AMRER03 force field. After 10 ns equilibration, each system was simulated at 298 K and pH 7.4 for a 25 ns production phase. Simulations were run twice for each molecular system. Results: By molecular dynamics simulations, the possibility was shown for polymyxin to form a stable complex with two neighbor structural domains of megalin in accord with the universal mechanism of binding the cationic ligands by ligand-binding CR repeats of the LDLR-family receptors. It was reported that interactions of megalin with polymyxin were stronger than with its derivative having no positively charged groups outside the macrocycle. The structural prerequisites of these differences were revealed, explaining the less nephrotoxicity of such derivatives compared to polymyxin. Conclusion: Comparative molecular dynamics simulations of megalin interactions with polymyxin B and its derivative NAB7061, which carries no positive charges outside the macrocycle, revealed the possible structural prerequisites for the lower nephrotoxic action of such polymyxin derivatives. The weakening of polymyxins binding with megalin may become an effective preventive measure against polymyxin-induced nephrotoxicity.
Keywords: megalin